Science and Prophetic Law: Karl Popper's Falsification Principle and Three Worlds of Science - Redhani, Muhammad Erfa (Universitas Islam Indonesia, 2024)
Kuntowijoyo has significantly influenced scholars in Indonesia, particularly in the realm of legal studies, through his concept of prophetic social science. This concept gave rise to Prophetic Law, a legal ideology that seeks to address societal issues by grounding legal principles in transcendental values. Prophetic Law emerges not just as a theoretical framework but as a practical ideology aimed at reforming and advancing legal science to solve contemporary problems. However, for Prophetic Law to be recognized as a valid and robust field of science, it must withstand rigorous testing, particularly through the process of falsification, as proposed by Karl Popper. This study aims to explore two critical aspects: first, the applicability of Popper's falsification theory to Prophetic Law, and second, the positioning and significance of Prophetic Law within Popper's three worlds of science. To investigate these aspects, a conceptual approach is employed, linking the principles of Prophetic Law with Popper's theories and delving into the philosophy of science to offer a comprehensive analysis. The study concludes that Popper's falsification principle is indeed relevant and necessary for testing the validity of Prophetic Law. Furthermore, in the context of Popper's three worlds of science, Prophetic Law currently resides in the second world, which is characterized by subjective ideas or what Popper refers to as